PANDEMIC COVID-19: IMPACT ON DIGITAL MARKETING - Omer, Mohammad (The journal of contemporary issues in business and government, 2021)
Covid-19 is the most widely used pandemic in the sector, a leading product in digital and digital media, including advertising, marketing and marketing. But Covid-1. The effect is mostly positive, not Covid-1. What other areas are about nations, human resources and tigers and so on. While the virus generates a lot of health insurance, social life, economic stability, jobs, etc. Intrastate, M., & Fuad, K. 2020, July stated that the list of customers and marketers. Covid-19 also leads to behavioral changes such as working remotely, spending a lot of time indoors, napping, learning recipes online, paying more attention to health and hygiene, prevention in Behavioral changes are particularly prevalent on digital platforms and digital content and create opportunities for marketers and brands to communicate digitally with customers more than ever. There has been an increase in social media engagement and the desire for digital content digital tools to sell many earning opportunities added Covid-1 at the same time. The strategy is based on the corporate strategy, and the strategy is based on the strategic aims of the company. The aim of this article is to highlight, analyze and understand the impact of the COVID-19 pandemic on digital marketing and advertising in general.